INCREASING MATHEMATICAL PROBLEM-SOLVING ABILITIES USING VIDEO TUTORIALS OF THE THREE-DIMENSIONAL COORDINATE SYSTEM IN SPATIAL ANALYTIC GEOMETRY - Silitonga, R H Yanti; Molle, Juliana Selvina; Ngilawajan, Darma Andreas (Universitas Pelita Harapan, 2023)
Because students were having trouble picturing the three-dimensional system of coordinates in a spatial analysis geometry course, their mathematical problem-solving abilities were still low. Educational movies that aid in visualization are essential for pupils. The study at hand used a design consisting of a pretest-posttest control group and was quasi-experimental in nature. While the control class experienced conventional teaching, the learners in the experimental group learned using three-dimensional coordinate system audiovisual media. A test of one's capacity to solve mathematical problems was used, along with observation sheets and interviews. A total of thirty-four participants made up the sample for this study, which was carried out at the University of Pattimura's Mathematics Education Study Program. Evaluation was of t-testing outcomes on mathematical problem-solving skills. The findings demonstrated that students' proficiency in solving problems with mathematics increased when they were taught to use a video about the three-dimensional coordinate system.